2009
DOI: 10.1007/s11182-009-9226-3
|View full text |Cite
|
Sign up to set email alerts
|

Spall fracture of coarse- and ultrafine-grained FCC metals under nanosecond high-current relativistic beam irradiation

Abstract: Experimental data are presented on the fracture mechanism and plastic deformation and thickness of the spalled layer obtained on irradiation of targets made from coarse-and fine-grained fcc metals (copper and aluminum) by a nanosecond high-current relativistic beam. The general and special features inherent in the modification of the microstructure of the spalled layer and near the surface of the spall fracture are discussed for the coarse-and fine-grained materials of the targets. Possible reasons for the var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…An answer to this question is also critical in terms of revealing the mechanism of spalling fracture of ultrafine-grained metals and alloys under high-density energy flows, and constructing its structural model. This work is an extension of the studies reported in [11,12] and provides a comparative analysis of the microstructure evolution and the mechanism of spalling fracture of a heterophase Al -5.5% Mg -2.2% Li -0.12% Zr (wt.%) alloy in its coarse-and ultra-fine-grained states under the action of a nanosecond relativistic high-current electron beam.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…An answer to this question is also critical in terms of revealing the mechanism of spalling fracture of ultrafine-grained metals and alloys under high-density energy flows, and constructing its structural model. This work is an extension of the studies reported in [11,12] and provides a comparative analysis of the microstructure evolution and the mechanism of spalling fracture of a heterophase Al -5.5% Mg -2.2% Li -0.12% Zr (wt.%) alloy in its coarse-and ultra-fine-grained states under the action of a nanosecond relativistic high-current electron beam.…”
Section: Introductionmentioning
confidence: 87%
“…These data were obtained at the strain rates less than 1·10 -1 s -1 in the region of moderate homological temperatures. Only more recent publications report deformation behavior and fracture of ultra-fine-grained metallic materials at the strain rates 10 4 -10 6 s -1 [8][9][10][11][12]. It should be noted that along with the high-speed impact of plates the authors of these studies used shock waves generated by the exposure to high-current electron beams.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The thickness of the spall layer increased almost linearly from 0.4 to 0.6 mm when the target thickness increased from 1.5 to 4 mm. This dependence is characteristic of the spallation of metal targets exposed to shock waves generated by nanosecond laser [12] and electron beams [10,11]. This is due to the fact that the amplitude of the shock wave that reached the back target surface is attenuated stronger with increasing target thickness.…”
Section: Shock-wave Loading and Rear Spallmentioning
confidence: 99%
“…To form shock waves, nanosecond ion [9] and electron beams with energy density of 10 10 -10 11 W/cm 2 [10,11] are typically used together with high-speed plate impact.…”
Section: Introductionmentioning
confidence: 99%